Alloiococcus otitidis Forms Multispecies Biofilm with Haemophilus influenzae: Effects on Antibiotic Susceptibility and Growth in Adverse Conditions - Chan, Chun L.; Richter, Katharina; Wormald, Peter-John; Psaltis, Alkis J.; Vreugde, Sarah (Frontiers in Cellular and Infection Microbiology, 2017)
Otitis media with effusion (OME) is a biofilm driven disease and commonly accepted otopathogens, such as Haemophilus influenzae, Streptococcus pneumoniae and Moraxella catarrhalis, have been demonstrated to form polymicrobial biofilms within the middle ear cleft. However, Alloiococcus otitidis (A. otitidis), which is one of the most commonly found bacteria within middle ear aspirates of children with OME, has not been described to form biofilms. The aim of this study was to investigate whether A. otitidis can form biofilms and investigate the impact on antibiotic susceptibility and survivability in polymicrobial biofilms with H. influenzae in vitro. The ability of A. otitidis to form single-species and polymicrobial biofilms with H. influenzae was explored. Clinical and commercial strains of A. otitidis and H. influenzae were incubated in brain heart infusion with and without supplementation. Biofilm was imaged using confocal laser scanning microscopy and scanning electron microscopy. Quantification of biofilm biomass and viable bacterial number was assessed using crystal violet assays and viable cell counting in both optimal growth conditions and in adverse growth conditions (depleted media and sub-optimal growth temperature). Antimicrobial susceptibility and changes in antibiotic resistance of single-species and multi-species co-culture were assessed using a microdilution method to assess minimal bactericidal concentration and E-test for amoxicillin and ciprofloxacin. A. otitidis formed single-species and polymicrobial biofilms with H. influenzae. Additionally, whilst strain dependent, combinations of polymicrobial biofilms decreased antimicrobial susceptibility, albeit a small magnitude, in both planktonic and polymicrobial biofilms. Moreover, A. otitidis promoted H. influenzae survival by increasing biofilm production in depleted media and at suboptimal growth temperature. Our findings suggest that A. otitidis may play an indirect pathogenic role in otitis media by altering H. influenzae antibiotic susceptibility and enhancing growth under adverse conditions.